Incidence and long-term outcomes of dextro-transposition of the great arteries (d-TGA) in the Kingdom of Bahrain - AlAraibi, Ahmed J.; Shakeeb, Fatema Naser; Shakeeb, Zahra Naser; Fredericks, Salim; Bhat, Aditya; Kalis, N. N. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundDextro-Transposition of the Great Arteries (d-TGA) is a rare cyanotic congenital heart defect requiring surgical correction for survival. The arterial switch operation (ASO) is the preferred approach, offering favorable long-term outcomes. However, long-term outcomes from the Gulf Cooperation Council (GCC) region remain largely unreported. This study presents the first national cohort from GCC, evaluating long-term surgical outcomes of d-TGA.MethodsA retrospective cohort study was conducted from 1983 to 2025. Patients were classified based on associated anomalies: simple d-TGA without major associated cardiac anomalies, d-TGA with ventricular septal defect (VSD), and d-TGA with left ventricular outflow tract obstruction (LVOTO). Kaplan–Meier analysis assessed survival and event-free survival (EFS).Results88 patients were included (male-to-female ratio 1.6:1). 20 were born to diabetic mothers, and 19 to consanguineous parents. Incidence rose over time, peaking at 2.58 per 10,000 live births. Median age at surgery declined to 27 days. Early mortality was 4.5%, with one postoperative ASO death. Reintervention was required in 35.2% of cases. Median EFS was highest in simple d-TGA (20.6 years), lowest after Rastelli repair (0.5 years). d-TGA with obstruction was statistically significant associated with postoperative left ventricular outflow obstruction (LVOTO), and simple d-TGA with right ventricular outflow obstruction (RVOTO).ConclusionThis is the first GCC-based study reporting long-term d-TGA outcomes. ASO remains the most effective intervention with superior survival and EFS. Consanguinity and maternal diabetes were key risk factors. Early diagnosis, close follow-up, and targeted public health interventions are essential to improving outcomes.